Policy of energy poverty alleviation and quality of life in Poland - Michal Litwinski (Institute of Economic Research (IER), 2016)
The aim of the article is to verify a hypothesis about positive influence of instrument of energy poverty alleviation policy on quality of life in Poland. In the article literature review is presented. There is also conducted quantitative analysis of data for 2004-2014. Variables regarding energy policy were obtained from OECD database, variables regarding quality of life - from Eurostat. The analysis confirmed that shaping one of the instruments of energy poverty alleviation policy - energy prices can positively affect access to electricity, thereby reducing scope and depth of energy poverty. Limitation of this phenomena could be a reason of quality of life increase.
Keywords: I31; C32; Q48; 330; energy policy; quality of life; energy prices